Transfer of innovation on allergic rhinitis and asthma multimorbidity in the elderly (MACVIA‐ARIA) ‐ EIP on AHA Twinning Reference Site (GARD research demonstration project). Issue 1 (24th August 2017) - Bousquet, J.; Agache, I.; Aliberti, M. R.; Angles, R.; Annesi‐Maesano, I.; Anto, J. M.; Arnavielhe, S.; Asayag, E.; Bacci, E.; Bedbrook, A.; Bachert, C.; Baroni, I.; et al.
Abstract: The overarching goals of the European Innovation Partnership on Active and Healthy Ageing (EIP on AHA) are to enable European citizens to lead healthy, active and independent lives whilst ageing. The EIP on AHA includes 74 Reference Sites. The aim of this study was to transfer innovation from an app developed by the MACVIA‐France EIP on AHA reference site ( Allergy Diary) to other reference sites. The phenotypic characteristics of rhinitis and asthma multimorbidity in adults and the elderly will be compared using validated information and communication technology (ICT) tools (i.e. the Allergy Diary and CARAT: Control of Allergic Rhinitis and Asthma Test) in 22 Reference Sites or regions across Europe. This will improve the understanding, assessment of burden, diagnosis and management of rhinitis in the elderly by comparison with an adult population. Specific objectives will be: (i) to assess the percentage of adults and elderly who are able to use the Allergy Diary, (ii) to study the phenotypic characteristics and treatment over a 1‐year period of rhinitis and asthma multimorbidity at baseline (cross‐sectional study) and (iii) to follow‐up using visual analogue scale (VAS). This part of the study may provide some insight into the differences between the elderly and adults in terms of response to treatment and practice. Finally (iv) work productivity will be examined in adults.